Entre a universidade e a escola: um estudo sobre estratégias de inserção de estudantes de educação física no território da escola durante a formação inicial - Locatelli, Tiago (Universidade do Vale do Rio dos Sinos, 2013)
This dissertation studies the initial training of the Physical Education teachers. The research is focused on the inclusion of Physical Education studentswithin the school and throughout the initial training. The objectives of the present study were: a) understand and discuss how the PE academics insertion occurs in the school environment; b) describe and analyze the strategies of Physical Education courses in order to include them into the school’s territory throughout the process of initial training; c) collate the understanding of the course coordinators and students about the productivity of such strategies for training teachers of Physical Education; d) contribute to the production of knowledge about the initial training of Physical Education teacher. The empirical field research was composed of two undergraduate courses in Physical Education of the state of Rio Grande do Sul and the research subjects were six academics and two course coordinators of degree in Physical Education from two private universities of Rio Grande do Sul. The information derived from empirical research was collected through semi-structured interview method. The presentation of the results and analysis of the information, especially prevalent qualitative aspects, were built from the following triangulation: the researcher's subjectivity; empirical field research; theoretical study. The data indicates that the main integration strategies are: a) apply lessons to fellow students; b) class of students / children attending the university for the academic exercise teaching; c) student goes to school and apply for part-time lessons for a specific class; d) the academic takes four or five children to implement activities in the university environment; e) mandatory curricular internship; f) jamborees; g) search for schools to act in an independent manner by academics; h) hours of observation; i) nonmandatory internships; j) required internships in pairs; l) institutional scholarship program for beginning teachers. The analysis points that the integration strategies contributed positively to the physical education student entry in the school universe. Although some of them follow a simplified model of achievement, under the premise of "throwing" the student of Physical Education into the school, I emphasize that these do not represent the consensus. However, it is important to highlight the structure and planning of others with the participation of the university, because these are not solitary strategies conducted exclusively by the students having minimal scrutiny and debate with the professor, besides performing a small ritual in and out of the school’s context. Finally, it was observed that one of the main integration strategies used by universities is found in conducting empirical researches are the required internships.
Keywords: Formação inicial de professores; Licenciatura em Educação Física; Escola; Initial teacher training; Degree in Physical Education; School; ACCNPQ::Ciências Humanas::Educação